First facts about American heroes - King, David C. (Woodbridge, Conn. : Blackbirch Press, 1996)
Introduces important people and events in American history, highlighting individuals who contributed to the nation's development over the centuries.
Includes bibliographical references (p. 104-105) and index.
Keywords: Heroes -- United States -- Biography -- Juvenile literature; United States -- History -- Juvenile literature; United States -- History